Survey of epiphytic microalgae to evaluate risk of ciguatera fish poisoning across natural and artificial reefs in North Carolina - Lim, Prisca; Paxton, Avery B.; Taylor, J. Christopher; Hall, Nathan S. (Frontiers in Marine Science, 2023)
Epiphytic microalgae are important contributors to the carbon and nutrient cycles yet are often overlooked during ecological surveys. In reef habitats, epiphytes are often found living on host organisms, including seaweeds or corals, and can influence community composition of higher trophic level taxa. Hence, understanding how epiphytes respond to different reef substrate materials can help inform designs of substrates intentionally deployed to form artificial reefs which can encourage high biodiversity and ecological functioning. One such epiphyte, Gambierdiscus spp., is a harmful benthic dinoflagellate which produces toxins that bioaccumulate and cause ciguatera fish poisoning (CFP) when contaminated fish is consumed by humans. CFP is one of the most frequently reported seafood-associated illnesses around the world, occurring most often near tropical reefs. We surveyed the epiphytes amongst 13 natural and artificial reef sites located off the coast of North Carolina to determine the role of the reefs’ foundational substrate (e.g., natural marl, steel or concrete) on structuring the epiphyte community with an emphasis on Gambierdiscus spp. abundance. No Gambierdiscus spp. were detected among the sampled reefs, likely due to suboptimal water temperatures. An ex-situ substrate preference experiment for Gambierdiscus spp. was performed using marl to represent natural rocky reefs, and steel and concrete to represent artificial reefs. Experimental results indicated that Gambierdiscus spp. grew fastest in the presence of marl and density decreased significantly when exposed to steel. However, steel artificial reefs had the highest average epiphyte biomass and species richness amongst the sampled reefs. 18s rRNA gene sequence analysis revealed that natural reefs were more likely to be dominated by dinoflagellates, whereas steel and concrete reefs were dominated by diatoms. We found that epiphyte composition was related to material at a phylum level, but seaweed hosts played a more significant role at the species level. These findings suggest that CFP risk is relatively low on the reefs studied but natural reefs would likely be preferentially colonized by Gambierdiscus spp. should ambient conditions become appropriate.